Universal Navigation on Smartphones - Karimi, Hassan A. (Springer US : Imprint: Springer, 2011)
Universal navigation is accessible primarily through smart phones providing users with navigation information regardless of the environment (i.e., outdoor or indoor). Universal Navigation on Smartphones provide the most up-to-date navigation technologies and systems for both outdoor and indoor navigation. It also provides a comparison of the similarities and differences between outdoor and indoor navigation systems from both a technological stand point and user's perspective. All aspects of navigation systems including geo-positioning, wireless communication, databases, and functions will be introduced. The main thrust of this book presents new approaches and techniques for future navigation systems including social networking, as an emerging approach for navigation.